If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14y + 1 = 1y + 27 Reorder the terms: 1 + 14y = 1y + 27 Reorder the terms: 1 + 14y = 27 + 1y Solving 1 + 14y = 27 + 1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 1 + 14y + -1y = 27 + 1y + -1y Combine like terms: 14y + -1y = 13y 1 + 13y = 27 + 1y + -1y Combine like terms: 1y + -1y = 0 1 + 13y = 27 + 0 1 + 13y = 27 Add '-1' to each side of the equation. 1 + -1 + 13y = 27 + -1 Combine like terms: 1 + -1 = 0 0 + 13y = 27 + -1 13y = 27 + -1 Combine like terms: 27 + -1 = 26 13y = 26 Divide each side by '13'. y = 2 Simplifying y = 2
| n-17=-13 | | 17n-70=168 | | 8x-10=8x-6 | | 42=4x+2x | | 4a+1=1a+25 | | f(x)=0.15x+5 | | 8y-5y=27 | | 5/3x-1=6/5x | | 6(x+30)=90 | | 8z-6=58 | | 5z+5=40 | | .2x+.6y=.52*80 | | 25=X+X+6 | | 1.5(x-4)=9.2 | | Y=3/4(x-3/4) | | Y=x(x+20) | | 3a^3/4-2a^3/4 | | 3y+2y+y+9x= | | 2n^2+4n-16=0 | | (3x-4)(-7x+4)=0 | | 2/(3-i) | | -4+4x=-8+10 | | -3(s+3)+10=8 | | 3x-18=y | | 3x+11=12-x | | x^2+8.4x-40=0 | | 2x+x+x+y+y= | | x^2-12x+36=13 | | 48-a=4-a+7 | | 2x-14+6x-9+3x+2=180 | | 6x^5-5=43 | | −2/3-7/8w=9/4 |